Sistem Informasi Akuntansi Penjualan Kredit Pada Yamaha Deta Singaparna - Siti Wahyuni, Ayu; Sofyan, Harnavela; Kausar Rahman, Lutfi (POLITEKNIK LP3I, 2025)
This study aims to determine how the implementation of the credit sales system at Yamaha Deta Singaparna Company in handling a sales transaction carried out on credit. The system is designed to provide convenience and speed in processing transactions carried out repeatedly by the company. The method used in this study is a descriptive qualitative method that will provide a description in the form of an overview of the credit sales information system running at Yamaha Deta Singaparna. A review of the implementation of the credit sales information system in this company can be said to have not been implemented well enough, that there are employees who perform several job functions concurrently, the availability of goods that are not recorded in detail, documents that are not yet effective for use, not filing documents properly, approval of the branch head for sales transactions that are still in the form of action approvals by not including documents to be authorized, and each section does not have a document archive, in addition, the document does not have a printed sequence number which aims to ensure that transactions can be monitored through documents used as a medium for recording transactions